2017
DOI: 10.15447/sfews.2017v15iss3art2
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Greenhouse Gas Emission Reductions and Economics of a Changing Agricultural Mosaic in the Sacramento–San Joaquin Delta

Abstract: We quantified the greenhouse-gas (GHG) emission and economic implications of alternative crop and wetland mosaics on a Sacramento-San Joaquin Delta island: Staten Island. Using existing GHG fluxes measurements for the Delta and biogeochemical models, we estimated GHG emissions for a range of scenarios, including the status quo, modified groundwater management, and incorporating rice and managed wetlands. For current land uses, emissions were predicted to vary greatly (48,000 to 105,000 t CO 2 -e yr -1 ) with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…We calculated a mean annual GWP of 1.86 Tg CO 2 e y −1 (range: 1.58-2.21 Tg CO 2 e y −1 ) for agricultural peatlands in the region, with N 2 O emissions representing 0.48 Tg CO 2 e y −1 (range: 0.28-0.77 Tg CO e y −1 ). Assuming the field estimates measured here are representative of local management practices, N 2 O fluxes alone could represent 26% (annual range: 18%-33%) of agricultural maize peatland CO 2 e emissions in this region, a significantly higher percentage than previous estimates (Deverel et al, 2017;Hemes et al, 2019). Soil types with similar organic matter content represent over 40,000 ha of agricultural peatlands in the Sacramento-San Joaquin Delta region (Deverel et al, 2016;Soil Survey Staff, 2020) and these soils are dominated by maize production.…”
Section: Upscaling Greenhouse Gas Emissionsmentioning
confidence: 82%
“…We calculated a mean annual GWP of 1.86 Tg CO 2 e y −1 (range: 1.58-2.21 Tg CO 2 e y −1 ) for agricultural peatlands in the region, with N 2 O emissions representing 0.48 Tg CO 2 e y −1 (range: 0.28-0.77 Tg CO e y −1 ). Assuming the field estimates measured here are representative of local management practices, N 2 O fluxes alone could represent 26% (annual range: 18%-33%) of agricultural maize peatland CO 2 e emissions in this region, a significantly higher percentage than previous estimates (Deverel et al, 2017;Hemes et al, 2019). Soil types with similar organic matter content represent over 40,000 ha of agricultural peatlands in the Sacramento-San Joaquin Delta region (Deverel et al, 2016;Soil Survey Staff, 2020) and these soils are dominated by maize production.…”
Section: Upscaling Greenhouse Gas Emissionsmentioning
confidence: 82%
“…With the recent development of the carbon methodology for Delta wetlands (Deverel et al 2017a), income is also available for demonstrated greenhouse gas emissions reductions in managed, permanently flooded wetlands and rice. Assessment of implementation of a mosaic of traditional crops (on low organic matter soils) and wetlands and rice (on high organic matter soils) on Staten Island demonstrated substantial greenhouse gas reduction benefit and profitability comparable with the status quo (Deverel et al 2017b). Such a mosaic could be applicable on other Delta islands.…”
Section: Discussionmentioning
confidence: 96%
“…Wetland drainage and subsidence is not unique to the Delta (Moomaw et al, 2018); many economically and ecologically important river deltas around the world are sinking at rates faster than sea levels are rising (Syvitski et al, 2009). The net climate benefit associated with restoration, however, is highly uncertain (Deverel et al, 2017;Hoper et al, 2008;Neubauer, 2014). The net climate benefit associated with restoration, however, is highly uncertain (Deverel et al, 2017;Hoper et al, 2008;Neubauer, 2014).…”
Section: 1029/2018gl077747mentioning
confidence: 99%
“…In order to avoid the large CO 2 emissions that result from oxidizing drained peat soils (Knox et al, 2015), subsided delta peatlands are currently being reflooded to harness a multitude of environmental benefits, including nutrient retention, habitat preservation, and storm protection, in addition to soil accretion through C sequestration (Himes-Cornell et al, 2018;Paustian et al, 2016). The net climate benefit associated with restoration, however, is highly uncertain (Deverel et al, 2017;Hoper et al, 2008;Neubauer, 2014).…”
Section: 1029/2018gl077747mentioning
confidence: 99%